Rasch Analysis: Differences in Student Achievment Motivation in Terms of Gender - Dony Darma Sagita; Shafna Utami Nur Fairuz (Universitas Ahmad Dahlan, 2021)
Achievement motivation is a sufficient factor important in determining ability within academic field. This research was conducted to see differences in achievement motivation in male students and female student. The data in this study are in the form of data politomi collected using instruments DAMS (Dds Achievment Motivation Scale). Research this involved 287 students consisting of 83 men and 204 women. Data analysis technique used is Mann Whitney combined with the RASCH model. Analysis results showed that there is a difference in achievement motivation. The results of this study shows that female students have high achievement motivation compared to students male. The results of this study contribute to guidance and counseling teachers in providing more intensive and effective services for students, especially male students who have lower achievement motivation than female students.